A hospital-based cost minimization study of the potential financial impact on the UK health care system of introduction of iron isomaltoside 1000 - Sunil Bhandari (Dove Medical Press, 2011)
Sunil BhandariDepartment of Renal Medicine, Hull and East Yorkshire Hospitals National Health Service Trust and Hull York Medical School, Kingston upon Hull, UKBackground: The clinical need to be able to administer high doses of intravenous iron conveniently in a single rapid infusion has been addressed by the recent introduction of ferric carboxymaltose and subsequently iron isomaltoside 1000. Neither requires a test dose. Ferric carboxymaltose can be administered at 15 mg/kg body weight to a maximum dose of 1000 mg, whereas iron isomaltoside 1000 can be administered at 20 mg/kg body weight. The ability to give high doses of iron is important in the context of managing iron deficiency anemia in a number of clinical conditions where demands for iron are high (including chronic blood loss associated with inflammatory bowel disease, menorrhagia, and chronic kidney disease). It is also an important component in the strategy as an alternative to a blood transfusion. Affordability is a key issue for health services.Methods: This study was a comparative analysis of the costs of administering the newly available intravenous iron formulations against standard practice (blood transfusion, intravenous iron sucrose) by considering the cost of this treatment option plus nursing costs associated with administration, equipment for administration, and patient transportation in the secondary care (hospital) setting across three dosage levels (600 mg, 1000 mg, and 1600 mg).Results and conclusion: The analysis indicates that the use of iron isomaltoside 1000 results in a net saving when compared with iron sucrose, blood, and ferric carboxymaltose. At 600 mg and 1000 mg doses, it is cheaper than low-molecular-weight iron dextran but more expensive at a dose of 1600 mg. However, it takes six hours to administer low-molecular-weight iron dextran at this dose level, which is inconvenient and reduces patient throughput (productivity).Keywords: iron isomaltoside 1000, iron deficiency anemia, high dose, single dose, parenteral iron, cost minimization